What roles does physical activity play following the death of a parent as a young person? A qualitative investigation - Jane Williams; Neil Howlett; Gillian W. Shorter; Julia K. Zakrzewski-Fruer; Angel Marie Chater (BMC, 2023)
Abstract Background Physical activity benefits physical and mental health. However, limited research investigates if physical activity can improve outcomes from the grieving process following the death of a parent. Methods Semi-structured interviews were conducted with 14 individuals (n = 8 female; age M = 31.2 years), who had experienced the death of a parent when they were aged between 10 and 24 years old, using retrospective recall. Data were analysed inductively using thematic analysis. Results Six themes were identified. Physical activity was seen as; 1) 'Therapeutic'; providing an 2) 'Emotional Outlet' and created a strong sense of 3) 'Social Support'. Alongside it 4) 'Builds Confidence', and led to 5) 'Finding Yourself' and 6) 'Improved Health and wellbeing' (physical and psychological). Conclusion Physical activity has the potential to provide positive experiences following a parental bereavement. It can provide a sense of freedom and was seen to alleviate grief outcomes, build resilience, enable social support and create a stronger sense of self. Bereavement support services for young people who have experienced death of a parent should consider physical activity as a viable intervention to support the grieving process.